Experimental Study and Mathematical Modeling of the Osmotic Drying Process - F. Shafiee Langari; K. Movagharnejad* (Iranian Journal of Chemical Engineering)
ne"> The osmotic dehydration of three agricultural products including carrot, zucchini and turnip has been studied in this research. The effect of several factors including temperature, sample to osmotic solution weight ratio and the concentration of the osmotic solutes on the osmotic dehydration of these agricultural products were investigated experimentally. The experimental studies consist of two different concentrations (10%, and 20 W/W% for carrots, 30%, and 50 W/W% for zucchini and 40%, and 50 W/W% for turnips), two different vegetable/solution weight to weight ratios (1:10 and 1:15 for all materials) and two different temperatures (30°C and 50°C for carrots and zucchini and 40°C and 50°C for turnips). Three dietary coatings including pectin, carboxymethyl cellulose and corn starch have been selected to control the solids uptake during the osmotic process. The Azuara model proved to be the most accurate correlation to describe the kinetics of the osmotic dehydration of these three agricultural products. The root mean square error of the Azuara model for solid gain in different conditions was between 0.014 and 0.065 for carrots, 0.011 and 0.030 for zucchini and 0.008 and 0.014 for turnips. The root mean square error of the Azuara model for water loss in different conditions was between 0.008 and 0.016 for carrots, 0.003 and 0.008 for zucchini and 0.009 and 0.017 for turnips.